The reverse of neodevelopmentalism: social conflicts around the pac works and the strategy of sectoral consensus - David Wallace Cavalcante (Tópicos Educacionais)
This article aims to problematize the challenges of the social experiences of union conflicts and not, whose car was the Growth Acceleration Program and its surroundings generated by the large projects of heavy civil construction, articulated and led by progressive governments.